Hexose transport in the apical and basolateral membranes of enterocytes in chickens adapted to high and low NaCl intakes - Garriga, Carles (Blackwell Science Inc, 1999)
1. The effect of a low-NaCl diet (LS diet) on the properties of hexose transport across the brush-border and basolateral membranes of enterocytes from jejunum, ileum and rectum of the chicken was investigated. 2. In the brush-border membrane, LS adaptation had no effect on K(m) for α-methyl-d-glucoside while V(max) values were significantly reduced in the ileum and in the rectum. All Scatchard plots of specific [(3)H]phlorizin binding give a straight line, consistent with a single population of binding sites. Phlorizin binding vs.α-methyl-d-glucoside maximal transport rates showed a linear correlation. 3. In the basolateral membrane, the LS diet did not modify the K(m) for d-glucose but reduced the V(max) in the ileum and in the rectum. Scatchard plots of [(3)H]cytochalasin B binding support the view that there is a single transport system in this membrane. There was a linear correlation between cytochalasin B binding and d-glucose V(max) values. 4. The response of the chicken intestine to LS intake consists of a dramatic reduction in the number of glucose transporters in both apical and basolateral membranes of the rectum, an intermediate response in the ileum and no significant effects in the jejunum.